Evaluation of occupational exposure to aerosol emitted from die sinking electrical discharge machining process. (7th May 2010) - Mathew, Jose; Sivapirakasam, S.P.; Surianarayanan, M.
Emission of toxic gases and aerosols is a critical occupational threat in the die sinking Electrical Discharge Machining (EDM) process. The present study is focused on the concentration of aerosols in the breathing zone of the EDM operator at various process parameters. Peak current, pulse duration, dielectric level and flushing pressure were the process parameters considered in this study, and the experiments were planned using a statistical tool known as Design of Experiment (DoE). The results of the experimental investigation indicated that the concentration of aerosol exceeded the Threshold Limit Values (TLV) specified by ACGIH for respirable particulates at higher values of peak current and pulse duration. The results obtained using DoE were helpful in correlating the characteristics of each variable of the process with the concentration of aerosol. The control measures to reduce the risk of aerosol exposure are also discussed in the paper.